Manajemen Sumber Daya Manusia Islam Bagi SDM di Bank Syariah - Trimulato Trimulato (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2018)
Sharia banking in Indonesia continues to experience growth both in terms of assets, the account of offices, the account of customers, and the market share of sharia banking that exceed 5 percent. The growth of sharia banking is not followed by adequate human resources both in quantity and quality. Human resources are still a difficult problem for sharia banking now. In the roadmap of sharia banking period 2015-2019 issued to make the Financial Services Authority to make human resource issues into things to be resolved. It takes a pattern of human resource management that can create qualified human resources for sharia banking. This paper is qualitative descriptive that will describe the growth of human resources in sharia banking, as well as the important role of Islamic human resource management for human resources in shariah banking. This paper shows the growth of human resources in sharia banking in the period of December 2016 until september 2017 grew by 2.368 percent, with the total human resources of shariah banking today as much as 61,389 people. The pattern of Islamic human resource management becomes important for the availability of best quality of human resources in sharia banking. Islamic human resource management able to meet the human resource who understand the science of economics and science of sharia. Islamic human resource management covers the entire process of establishing human resources in sharia banking. One of the patterns of Islamic human resource management that is relevant to the current state of sharia banking is Calestial Management. It consists of ZIKR, PIKR, and MIKR.